2019
DOI: 10.1155/2019/2651037
|View full text |Cite
|
Sign up to set email alerts
|

Weiqi Decoction Attenuated Chronic Atrophic Gastritis with Precancerous Lesion through Regulating Microcirculation Disturbance and HIF-1α Signaling Pathway

Abstract: Aim. Chronic atrophic gastritis (CAG), the precancerous lesions of gastric cancer, plays an important role in the stepwise process of gastric cancer. The ancient Chinese medicine believes in that Qi deficiency and blood stasis are involved in the pathogenesis of CAG. Weiqi decoction, a classical formula from Longhua Hospital, could supplement Qi and activate blood circulation of human beings and has been used for treating CAG in clinic over twenty years. The study aims to clarify the effect and underlying mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…It is used for GPL treatment and fortifies the spleen, removes blood stasis, and harmonizes the stomach [67]. Experimental studies have shown that Weiqi decoction had an inhibitory effect on gastric inflammation by reducing COX-2 and increasing PGE2 in chronic atrophy gastritis rats with precancerous lesions [39]. Among the decoctions, herbs such as Radix Angelicae Sinensis [68], Radix Astragali [69], Radix Codonopsis [70], and Rhizoma Curcumae [71] were reported to exert anti-inflammatory effects by modulating the release of inflammatory mediators, which indicated that attenuating the inflammatory injury is a key mechanism of Weiqi decoction in the treatment of GPL.…”
Section: Therapeutic Mechanisms Of Tcm In Gplmentioning
confidence: 99%
See 2 more Smart Citations
“…It is used for GPL treatment and fortifies the spleen, removes blood stasis, and harmonizes the stomach [67]. Experimental studies have shown that Weiqi decoction had an inhibitory effect on gastric inflammation by reducing COX-2 and increasing PGE2 in chronic atrophy gastritis rats with precancerous lesions [39]. Among the decoctions, herbs such as Radix Angelicae Sinensis [68], Radix Astragali [69], Radix Codonopsis [70], and Rhizoma Curcumae [71] were reported to exert anti-inflammatory effects by modulating the release of inflammatory mediators, which indicated that attenuating the inflammatory injury is a key mechanism of Weiqi decoction in the treatment of GPL.…”
Section: Therapeutic Mechanisms Of Tcm In Gplmentioning
confidence: 99%
“…Caspase-3 and Ki67 are considered apoptosis and proliferative cell markers in tumor formation, respectively [82,83]. A recent study showed that the Weiqi decoction introduced above could enhance the protein expression of cleaved caspase-3 and decrease the protein expression of Ki67 in pyloric gastric mucosa in GPL rats, indicating that this decoction could regulate the imbalance of proliferation and apoptosis [39]. Ginkgo biloba is an ancient herb that has been used for thousands of years in China.…”
Section: Regulating the Proliferation And Apoptosis Of Gplmentioning
confidence: 99%
See 1 more Smart Citation
“…It has several bene ts such as its satisfactory curative effects, and its low prevalence of side effects and cost, and has been gradually accepted by the public both in China and internationally [9][10][11][12][13]. Studies have shown that Chinese herbal compounds can regulate cell apoptosis via multiple pathways [14], can reduce the angiogenesis response of rats with precursor lesions, alleviate microvascular abnormalities [15] and regulate blood ow disorders which can delay, block, or reverse the development of precursor lesions [16]. This demonstrates the bene ts of TCM and highlights the great potential of Chinese herbal compounds for the treatment and prevention of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to chemical drugs, traditional Chinese medicine (TCM) has a unique advantage in the treatment of CAG and produces no serious side effects [16] . For example, Weiqi Decoction attenuated CAG with precancerous lesions by regulating the disturbed gastric mucosal blood flow and the HIF-1 signaling pathway [17] . Tian G et al [18] adopted immune repertoire sequencing techniques to evaluate the effect of Modified Sijunzi Decoction for treating CAG.…”
mentioning
confidence: 99%